MYCOBACTERIOSIS: THE PAST AND PRESENT - Stamenković, Zoran; Ristic, Lidija; Stankovic, Ivana; Radovic, Milan; Golubovic, Slavica; Ivanovic Djordjevic, Vesna; Matejic, Ivan (Acta medicae Medianae, 2022)
Non-tuberculous mycobacteria (NTM) are ubiquitous organisms, they are found everywhere in the vicinity. Humans are in everyday contact with these microorganisms. Although tuberculosis (TB) cases have been declining worldwide, there is a growing incidence of NTM infections. NTM may cause both asymptomatic infection and symptomatic disease in humans. The most common are pulmonary infections of varying severity. Accurate diagnosis is of crucial importance because the treatment medications may have serious adverse effects, among other things. The treatment of mycobacteriosis is not directly analogous to the treatment of tuberculosis. Empiric therapy is not recommended. In vitro susceptibility of many NTM does not correlate with clinical response to antimycobacterial drugs.